Antropometri Pada Ruang Serba Guna Rumah Tipe 21 - Carina Sarasati; Taufiq Rizza Buzuluddin (Neo Teknika, 2021)
Currently, subsidized housing programs for low-income people are widely offered to the community, one of the smallest types of floor plans offered is type 21/60 houses. However, in its development, the floor plan offered by the developer is different from the standard technical guidelines that have been set by the Government. This research was conducted to see whether the multipurpose room on the type 21/60 house plan, either according to the Technical Instructions of the Department of Settlement and Regional Infrastructure or the subsidized house offered by the developer, was ready for habitation and in accordance with the anthropometry of the Indonesian human body (in this study 2 male adults and one adult male woman). The research method used is descriptive qualitative with comparative descriptive analysis techniques. The results of this study stated that the type 21/60 house plan according to the Technical Instructions of Pt S-02-2000- C and the case study object was in accordance with the anthropometry of the Indonesian human body, but there were several activities that could not be carried out simultaneously. Keywords: anthropometry, multipurpose room, type 21 house